(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the impact of family separation on the psychological development of children. The emotional states, behavioral changes, and social adaptation problems that arise in children during the separation process are examined. Research shows that parental separation affects the child’s psyche to varying degrees, and this impact depends on the child’s age, family environment, and the parents’ attitude. The article also provides recommendations for reducing the consequences of separation.